Influence of question type on response adequacy in young adults with autism - Hewitt, Lynne E (Journal of communication disorders, 1998)
Sources of difficulty in comprehending conversational questions for individuals with autism may be multifarious, given the complexity of the disorder. This study investigated success in responding to naturalistic conversational questions by six young adults with autism, using a quantitative discourse analytic method. Subjects, aged 19–21, who were able to converse in at least simple sentences, were engaged in conversation about events and activities in their lives. From the transcripts of these conversations, four types of questions were isolated for analysis: more than seven words in length; multiclausal; requiring inference; and indirect requests for information. It was predicted that inference-based questions would be more difficult than the other types. Findings did not support this prediction. All four types showed a higher failure rate than the overall failure rate for responses to conversational questions. Clinical implications include the need for conversational assessment of receptive language functioning for individuals with autism. Suggestions for such assessments are provided.